Investigation of the effects of heat treatment parameters during synthesis of titanium-magnesium-based Ziegler-Natta catalysts. Issue 5 (9th April 2021) - Jandaghian, Mohammad Hossein; Maddah, Yasaman; Nikzinat, Ehsan; Masoori, Maryam; Sepahi, Abdolhannan; Rashedi, Reza
Abstract: Many researchers have studied the effects of donors, promoters and alkyl aluminum compounds on the polymerization catalysts, the polymerization process and the final properties of polymers. Nevertheless, changing the operating parameters (such as temperature, duration and order of steps) during the catalyst synthesis process is an industrially popular solution to the challenge of modifying Ziegler-Natta catalysts (without adding, removing, or changing raw materials). In the present study, the effects of important heat treatment parameters such as titanation temperature, tempering time and tempering temperature, are systematically considered during the synthesis of a titanium-magnesium-based Ziegler-Natta catalyst. The results show that using harsher conditions during the titanation or tempering phase leads to less active catalysts that can be used to produce higher molecular weight polyethylene chains. Moreover, the tempering time was determined as the most important parameter for controlling the activity of the catalysts and the molecular weight of the final polymers. Finally, it was found that setting the tempering time at a certain level, regardless of the magnitude of the other parameters, leads to the production of catalysts at a unique level of activity. Graphical abstract: